Gu li xin yan - Yang, Hua 1967- (Shang wu yin shu guan, 2012)
Summary in vernacular field only
Keywords: Geschichte Anfänge-221 v. Chr.; Rites and ceremonies / China; Inscriptions, Chinese / History and criticism; Inscriptions, Chinese; Manners and customs; Rites and ceremonies; Ritus; Inschrift; China / Social life and customs / To 221 B.C.; China